Preliminary Observations on Natural Regeneration of Chir in Seed Production Area Vis-a-vis Natural Stand of Pinus roxburghii at High Elevation - Bahar, N.; Naithani, K. C.; Chauhan, Y. S. (Indian Forester, 2003)
No abstract